Effectiveness of Acceptance and Commitment Therapy Based on Positive Psychology Approach on Rumination and Positive and Negative Meta-emotions in Anxious Women - Anisian, Mehrasa; Dasht Bozorgi, Zahra; Mirzaie, Negar (Psychology of Woman Journal, 2024)
Objective: This research was conducted with the purpose of examining the effectiveness of acceptance and commitment therapy (ACT) based on a positive psychology approach on rumination and both positive and negative meta-emotions in anxious women. Methods and Materials: The study employed a quasi-experimental design. The population consisted of all anxious women in Tehran in the year 2022, from which 30 individuals were selected as the sample. Fifteen participants were placed in the experimental group and fifteen in the control group. The instruments used for data collection were the Rumination Questionnaire and the Meta-emotions Questionnaire. Findings: Data analysis was conducted using covariance analysis tests. The results indicated that the intervention of acceptance and commitment therapy based on a positive psychology approach has a significant effect on rumination and positive and negative meta-emotions in anxious women (p < 0.05). Conclusion: Therefore, acceptance and commitment therapy based on the positive psychology approach can be utilized for anxious women.